Application Of Starch Edible Coating Which Added Asam Kandis Extract (Garcinia Xanthochymus) To Pear Fruit (Pyrus Pyrifolia) Minimally Process - Widyaka, Vetra Hendrawan (University of Brawijaya, 2019)
Minimally process is higher risk to pear fruit so itâ€™s need to some preserve action that make quality and shelf life longer. The one method that we can use is using edible coating application. The purpose of this research is for make pear minimally process have shelf-life untill the sixth day and know optimum concentration of asam kandis extract which applicated in edible coating solution. This research, tapioka starch and asam kandis extract is main ingridient. Starch tapioka edible coating with added asam kandis extract can make longer pear with minimally process untill the sixth day in the cold temperature. Design of experimental of this research is Completly Randomized Design with asam kandis extract variaton which added in solution edible coating with concentration 0,25%; 0,5%; and 0,75%. Factorial Completly Randomized Design with two factor of variation, the first factor is control, edible coating, and edible coating asam kandis. The second factor is storage time (Day 0, 2, 4, and 6). The best result of Â inhibitory zone of edible coating which added with asam kandis extract is 0,5% concentration and the best layering with edible coating application added with extract asam kandis can keep the pear with minimally process untill sixth day, preserve moisture content, texture, browning, reduce Total Plate Count (TPC) and have a good result in organoleptic test.